2015
DOI: 10.4172/1948-5956.1000375
|View full text |Cite
|
Sign up to set email alerts
|

An Additional risk of Lung Cancer from Recurrent Exposure to Ethyl Carbamate (EC) in BALB/C Mice

Abstract: Ethyl carbamate (EC); urethane is a chemical carcinogen (IARC group 2A). It has been commonly found in the fermented food and beverages. EC induced cancerous lesion in different sites due to the formation of active metabolite; vinyl carbamate (VC). The current study aims to investigate the potential risk of cancerous lesions in small and repeated exposure of ethyl carbamate in BALB/C mice. Three groups of BALBL/C mice were treated for 120 days included untreated control; group treated with a single dose of ure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The selected dose of urethane was based on previous work was conducted by (Hamzawy et al, 2015). The results of the current study revealed that urethane induced significant increase of LDH activities that indicated by increase in cellular proliferation and cancer promotion.…”
Section: Histological Examinationsmentioning
confidence: 83%
See 1 more Smart Citation
“…The selected dose of urethane was based on previous work was conducted by (Hamzawy et al, 2015). The results of the current study revealed that urethane induced significant increase of LDH activities that indicated by increase in cellular proliferation and cancer promotion.…”
Section: Histological Examinationsmentioning
confidence: 83%
“…Lung cancer was induced by intraperitoneal injection of urethane (ethyl carbamate) (1.5 mg/kg b.w) two times; once at the first and eighth week (Hamzawy et al, 2015).…”
Section: Induction Of Lung Cancermentioning
confidence: 99%